Dynamic Changes in Sensory Quality and Chemical Components of Bingdao Ancient Tree Tea During Multiple Brewing - Chunju Peng; Yuxin Zhao; Sifeng Zhang; Yan Tang; Li Jiang; Shujing Liu; Benying Liu; Yuhua Wang; Xinghui Li; Guanghui Zeng (Foods, 2025)
Bingdao ancient tree tea (BATT), a type of raw Pu-erh tea, is renowned for its brewing durability, characterized by a unique aroma and flavor. To explore the dynamic changes in infusion quality and the impact of multiple steeping process, BATT was brewed 14 times, and its sensory attributes, infusion color, and chemical composition were assessed across different brewing intervals. The color of the tea infusion remained relatively stable throughout the brewing process. Sensory evaluation indicated that BATT exhibited optimal sensory quality between the third and seventh infusions. While the leaching of polyphenols showed minimal variation across brews, the concentrations of ester-catechins, non-ester catechins, free amino acids, and caffeine after the seventh brewing decreased by 28.82%, 21.83%, 28.86%, and 40.37%, respectively. Our results indicated that higher concentrations of flavor compounds in the BATT infusion appeared between the fourth and seventh brews. This study provides a theoretical basis for understanding the brewing characteristics of BATT.